Ferritin nanocage loading lycopene for improving blood-brain barrier transcytosis and attenuating D-galactose-induced apoptosis in PC12 cells - Xiaoyu Xia; Han Li; Xianbing Xu; Zhenyu Wang; Junjie Yi; Guanghua Zhao; Ming Du (Food Science and Human Wellness)
Aging is a physiological process that leads to degeneration and functional decline of the brain. This is accompanied by intracellular peroxidation and neuronal apoptosis. Natural antioxidants possess a remarkable effect on attenuating the oxidative stress cascade and apoptosis of neurons; however, the challenge of using natural antioxidants for neuroprotection is fabricating a delivery system to overcome the blood-brain barrier (BBB) transport. Herein, we successfully created a stable delivery platform built on rigid ferritin nanocage loading natural lycopene molecules, crossing the BBB in quantity and being taken up in neurons. This nanoparticle worked on D-galactose-induced senescence via alleviating neuronal hyperoxidation injury and weakening neuronal apoptosis in PC12 and BV2 cells. More importantly, this natural delivery system possesses inherent biocompatibility and potential application in improving the bioavailability of bioactive edible compounds with low water solubility. This study demonstrated the effectiveness of natural antioxidant nanomedicines in maintaining the defenses of intracerebral peroxidation and improve degenerating neurons, providing the potential to combat further imbalances of neuronal microenvironment in aging neuropathy.